The comic book style of the poetical subject in the contemporary Croatian poetry of intermedial and postintermedial experience - Jukić, Sanja (Poznańskie Studia Slawistyczne, 2012)
This paper deals with poetic subjects in the comic book format as presented in the media. The subject of media entity dominates the corpus of texts in intermedial and post-intermedial poetry experience. These aspects of Croatian poetry from 1968 up to the present day, whose structures are primarily determined by contacts with different media culture texts, are defined by Goran Rem. This paper explores the ways in which the media inter-mediates comic book semiotics into the poetic code of that particular part of contemporary Croatian poetry and thus determines the paradigmatic forms of the subject of media/comic book.